2022
DOI: 10.1001/jamacardio.2022.2496
|View full text |Cite
|
Sign up to set email alerts
|

Alerting Clinicians to 1-Year Mortality Risk in Patients Hospitalized With Heart Failure

Abstract: Heart failure is a major cause of morbidity and mortality worldwide. The use of risk scores has the potential to improve targeted use of interventions by clinicians that improve patient outcomes, but this hypothesis has not been tested in a randomized trial.OBJECTIVE To evaluate whether prognostic information in heart failure translates into improved decisions about initiation and intensity of treatment, more appropriate end-of-life care, and a subsequent reduction in rates of hospitalization or death. DESIGN,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 26 publications
(35 reference statements)
1
16
0
Order By: Relevance
“…Consistently, a recent study showed that, in patients with severe exercise limitation, the peak VO 2 measured by a portable device allowing breath-by-breath measurement of cardiorespiratory parameters during a standard 6MWT is similar to -or even higher than-that reached in CPET [37].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Consistently, a recent study showed that, in patients with severe exercise limitation, the peak VO 2 measured by a portable device allowing breath-by-breath measurement of cardiorespiratory parameters during a standard 6MWT is similar to -or even higher than-that reached in CPET [37].…”
Section: Discussionsupporting
confidence: 62%
“…Two recently published randomized clinical trials performed in the acute care setting provided somewhat con icting results. The Risk Evaluation and its Impact on Clinical Decision Making and Outcomes in Heart Failure (REVEAL-HF) study, investigated whether provision of 1-year mortality estimates during HF hospitalization affects outcomes in patients hospitalized for HF [37]. There was no evidence that information about risk affected the rate of 30-day hospital readmissions and mortality, prescription of HF medications at discharge, or 1-year mortality.…”
Section: Discussionmentioning
confidence: 99%
“…A novel, targeted EHR-based alerting system for outpatients with heart failure with reduced ejection fraction led to significantly higher rates of guideline-directed medical therapy at 30 days compared with usual care [ 17 ]. On the other hand, there were no significant differences in key patient outcomes (30-day hospitalization, 1-year mortality, or adherence to guideline-directed medical therapy) among patients who had a 1-year mortality risk prediction rate displayed to their inpatient providers [ 18 ]. This finding suggests that prognostic information alone (without paired decision support) does not change practice or outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of a new risk tool and clinical decision support (CDS) into a busy ED can be challenging [ 14 , 15 , 16 ]. EHR tools for patients with AHF have been successfully deployed, with limited impacts observed when decision support was not added to prognostic scores [ 17 , 18 ]. Prior studies highlight an underappreciation of the steps needed to translate model predictions into real-time use and improved health [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Improving Quality Improvement-From Aspiration Toward Empiricism Andrew S. Oseran, MD, MBA; Rishi K. Wadhera, MD, MPP, MPhil In this issue of JAMA Cardiology, Ahmad and colleagues 1 report the results of their pragmatic, multicenter, electronic health record (EHR)-based, randomized clinical trial The Risk Evaluation and Its Impact on Clinical Decision-making and Outcomes in Heart Failure (REVEAL-HF), which was designed to evaluate whether providing clinicians with patient-specific prognostic information improved care for individuals hospitalized with heart failure. The authors randomly assigned 3124 patients across 4 hospitals to either usual care or the intervention, an EHR alert directed at treating physicians that displayed predicted 1-year mortality rates.…”
Section: Invited Commentarymentioning
confidence: 99%